Genetic relationships of body condition score with carcass traits in Limousin cattle - Eborn, D.R.; Moser, Daniel W. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Field data from the North American Limousin Federation was used to determine the heritability and genetic correlations of body condition score (BCS) with carcass traits. Carcass traits included carcass weight, ribeye area, fat thickness, intramuscular fat, and % kidney, pelvic, and heart fat, and all were estimated to be lowly to moderately heritable (0.14 to 0.34). Heritability of BCS was 0.19. Favorable correlations existed between ribeye area and carcass weight (0.50), ribeye area and BCS (0.60), and carcass weight and BCS (0.28). Unfavorable correlations existed among ribeye area and intramuscular fat (-0.40), carcass weight and intramuscular fat (-0.23), and intramuscular fat and BCS (-0.64). These results suggest that selection for BCS should be effective and would result in some favorable changes in ribeye area and carcass weight but with unfavorable change in marbling.
Keywords: Beef; Body condition score (BCS); Carcass traits; Limousin cattle